The Distribution of Microalgae in a Stabilization Pond System of a Domestic Wastewater Treatment Plant in a Tropical Environment (Case Study: Bojongsoang Wastewater Treatment Plant) - Herto Dwi Ariesyady; Rifka Fadilah; Kurniasih Kurniasih; Aminudin Sulaeman; Edwan Kardena (Journal of Engineering and Technological Sciences, 2016)
The Bojongsoang Wastewater Treatment Plant (WWTP) serves to treat domestic wastewater originating from Bandung City, West Java, Indonesia. An abundant amount of nutrients as a result of waste decomposition increases the number of microalgae populations present in the pond of the wastewater treatment plant, thereby causing a population explosion of microalgae, also called algal blooming. In a stabilization pond system, the presence of algal blooming is not desirable because it can decrease wastewater treatment performance. More knowledge about the relationship between the nutrients concentration and algae blooming conditions, such as microalgae diversity, is needed to control and maintain the performance of the wastewater treatment plant. Therefore this study was conducted, in order to reveal the diversity of microalgae in the stabilization pond system and its relationship with the water characteristics of the comprising ponds. The results showed that the water quality in the stabilization pond system of Bojongsoang WWTP supported rapid growth of microalgae, where most rapid microbial growth occurred in the anaerobic pond. The microalgae diversity in the stabilization ponds was very high, with various morphologies, probably affiliated with blue-green algae, green algae, cryptophytes, dinoflagellates and diatoms. This study has successfully produced information on microalgae diversity and abundance profiles in a stabilization pond system.